Postoperative circulating tumor DNA detection is associated with the risk of recurrence in patients resected for a stage II colorectal cancer - Grancher, Adrien; Beaussire, Ludivine; Manfredi, Sylvain; Le Malicot, Karine; Dutherage, Marie; Verdier, Vincent; Mulot, Claire; Bouché, Olivier; Phelip, Jean-Marc; Levaché, Charles-Briac; Deguiral, Philippe; Coutant, Sophie; et al. (Frontiers in Oncology, 2022)
Circulating tumour DNA (ctDNA) is reported to be promising in localized colorectal cancer (CRC). The present study aimed to retrospectively evaluate the impact of ctDNA in patients with a resected stage II CRC from the PROGIGE 13 trial with available paired tumour and blood samples. A group of recurrent patients were matched one-to-one with nonrecurrent patients according to sex, tumour location, treatment sequence, and blood collection timing. CtDNA was analysed by digital PCR according to NGS of tumours. Disease-free survival (DFS) and overall survival (OS) were analysed based on ctDNA, and the risks of recurrence and death were determined. A total of 134 patients were included, with 67 patients in each group. At least one alteration was identified in 115/134 tumours. Postoperative ctDNA was detected in 10/111 (9.0%) informative samples and was detected more frequently in the recurrent group (16.7% versus 1.8%; p = 0.02). The median DFS of ctDNA+ versus ctDNA- patients was 16.8 versus 54 months (p = 0.002), respectively, and the median OS was 51.3 versus 69.5 months (p = 0.03), respectively. CtDNA was associated with recurrence (ORa = 11.13, p = 0.03) and death (HRa = 3.15, p = 0.01). In conclusion, the presence of postoperative ctDNA is associated with both recurrence and survival in stage II CRC.